Revitalizing Agricultural Waqf for Sustainable Food Security: A Comparative Study of Indonesia and Turkey - Muizz, Abdul; Kassim, Salina; Noordin, Nazrul Hazizi (Al-Mustashfa: Jurnal Penelitian Hukum Ekonomi Syariah, 2025)
Agricultural waqf represents a strategic instrument of Islamic social finance with the potential to support sustainable food security through asset-based and risk-sharing mechanisms. This study aims to analyze and compare agricultural waqf models in Indonesia and Türkiye, focusing on institutional governance, integration with Islamic finance, and their implications for food security outcomes. Using a qualitative comparative case-study approach, the research draws on document analysis, regulatory review, and semi-structured interviews with waqf stakeholders in both countries. The findings reveal that the effectiveness and scalability of agricultural waqf are determined less by land availability than by institutional quality, particularly nazhir professionalism, regulatory coherence, and state–market coordination. Indonesia’s agricultural waqf remains fragmented, characterized by weak documentation, limited financial integration, and reliance on voluntary management, while Türkiye demonstrates a more standardized and centralized governance legacy rooted in Ottoman waqf institutions. The study further finds that productive agricultural waqf requires a full-cycle financing architecture, in which zakat provides initial de-risking support, waqf functions as an asset-based risk absorber, and Islamic commercial finance supplies profit-sharing working capital through Shariah-compliant contracts such as muzāra‘ah and ijārah. Evaluated through the lens of maqāṣid al-sharī‘ah, particularly ḥifẓ al-nafs and ḥifẓ al-māl, agricultural waqf can contribute to sustainable food security when embedded within integrated value chains and outcome-oriented governance frameworks aligned with SDG 2.Keywords: agricultural waqf; sustainable food security; Islamic social finance; maqāṣid al-sharī‘ah; Indonesia–Türkiye comparison